Ionospheric radio propagation - Davies, Kenneth (U.S. Department of Commerce, 1965)
The earth´s atmosphere, geomagnetism and the sun - Theory of wave propagation - Synoptic studies of the ionosphere - Oblique propagation - Signal strength - Ionospheric disturbances - Ionospheric propagation predictions - Scatter propagation on very high frequencies - Propagation of low and very low frequency waves.